The 4-Aminopyridine Model of Acute Seizures in vitro Elucidates Efficacy of New Antiepileptic Drugs - Heuzeroth, Hanno; Wawra, Matthias; Fidzinski, Pawel; Dag, Ramazan; Holtkamp, Martin (Frontiers in Neuroscience, 2019)
Up to date, preclinical screening for new antiepileptic substances is performed by a combination of different in vivo models of acute seizures, for which large numbers of animals are necessary. So far, little attention has been paid to in vitro models, which are also able to detect antiepileptic efficacy and in principle could likewise serve for exploratory preclinical screening. One of the established in vitro models of acute seizures is the 4-aminopyridine (4-AP) model. Previous studies have shown that the 4-AP model is capable to recapitulate the antiepileptic efficacy of standard antiepileptic drugs such as valproate or carbamazepine. Here, we employed a dual methodological approach using electrophysiology and optical imaging to systematically test the antiepileptic efficacy of three new-generation antiepileptic drugs with distinct mechanisms of action (lacosamide, zonisamide, and levetiracetam). We found that frequency of 4-AP induced seizure like events (SLE) was the most sensitive parameter to detect dose-dependent antiepileptic effects in these compounds. Specifically, levetiracetam reduced SLE frequency while lacosamide and zonisamide at higher doses completely blocked SLE incidence. Analysis of the intrinsic optical signal additionally revealed a subiculum-specific reduction of the area involved in the propagation of ictal activity when lacosamide or zonisamide were administered. Taken together, our data adds some evidence that acute seizure models in vitro are in principle capable to detect antiepileptic effects across different mechanisms of action with efficacy similar to acute models in vivo. Further studies with negative controls, e.g. penicillin as a proconvulsant, and other clinically relevant antiepileptic drugs are needed to determine if this acute in vitro model might be useful as exploratory screening tool. In view of the increasing sensitivity towards animal welfare, an affective in vitro model may help to reduce the number of laboratory animals deployed in burdening in vivo experiments and to preselect substances for subsequent testing in time- and cost-laborious models of chronic epilepsy.